The shadow economy in industrial countries - Dominik Enste (IZA World of Labor, 2018)
The shadow (underground) economy plays a major role in many countries. People evade taxes and regulations by working in the shadow economy or by employing people illegally. On the one hand, this unregulated economic activity can result in reduced tax revenue and public goods and services, lower tax morale and less tax compliance, higher control costs, and lower economic growth rates. But on the other hand, the shadow economy can be a powerful force for advancing institutional change and can boost the overall production of goods and services in the economy. The shadow economy has implications that extend beyond the economy to the political order.
Keywords: O17; K42; J22; H26; 330; shadow economy; underground economy; informal economy; illicit work